2019
DOI: 10.1071/an17102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunocastration on the performance and meat quality traits of feedlot-finished Bos indicus (Nellore) cattle

Abstract: This study aimed to evaluate the effects of immunocastration on the performance, testosterone concentration, carcass traits and meat quality of feedlot-finished Nellore cattle. Fifty-eight males (430 ± 36 kg bodyweight; 24 months old) were separated into three groups in a randomised complete design: surgically castration (n = 15), immunocastrated (anti-gonadotropin-releasing hormone (Bopriva®) vaccine, n = 21) and non-castrated (n = 22). The animals were housed in individual pens and fed ad libitum for 90 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
3
9
0
2
Order By: Relevance
“…Immunocastration has been also related to the lower muscle mass deposition (Dunshea et al, 2005;Walker et al, 2010;Amatayakul-Chantler et al, 2013;Gómez et al, 2017). The results observed in this study are in a good agreement with this statement, since immunocastrated animals presented a lower serum creatinine and CK concentration than non-castrated animals.…”
Section: Immunocastration Effectssupporting
confidence: 90%
See 3 more Smart Citations
“…Immunocastration has been also related to the lower muscle mass deposition (Dunshea et al, 2005;Walker et al, 2010;Amatayakul-Chantler et al, 2013;Gómez et al, 2017). The results observed in this study are in a good agreement with this statement, since immunocastrated animals presented a lower serum creatinine and CK concentration than non-castrated animals.…”
Section: Immunocastration Effectssupporting
confidence: 90%
“…Several researchers have reported that immunocastration increased fat deposition in the carcass of beef cattle (Dunshea et al, 2005;Amatayakul-Chantler et al, 2012Gómez et al, 2017). These results were also observed in this study, in which immunocastrated animals had greater serum HDL and triglycerides concentrations than non-castrated animals.…”
Section: Immunocastration Effectssupporting
confidence: 89%
See 2 more Smart Citations
“…Immunocastration creates specific antibodies that recognize and bond to the hormone GnRH-I, preventing bonding with pituitary receptors, thus inhibiting FSH and LH secretion, causing infertility [10,12]. Thus, immunocastration has proven inhibition of reproductive activity in pigs [13][14][15], cattle [16,17], horses [18], sheep [19], mice [20][21][22][23], camelids [24], cats [25], chickens [26], and dogs [9,27,28]. Bansal and collaborators (2019) have recently developed and proven that immunogenicity of a vaccine able to develop immunity against GnRH and rabies virus simultaneously in mice [29].…”
Section: Introductionmentioning
confidence: 99%